Dual fluorescent aptasensor for simultanous and quantitative detection of sulfadimethoxine and oxytetracycin residues in animal-derived foods tissues based on mesoporous silica - Tang, Jiaming; Zheng, Xiaoling; Jiang, Shuang; Cao, Mingdong; Wang, Sixian; Zhou, Zhaoyang; Nie, Xunqing; Fang, Yu; Le, Tao (Frontiers in Nutrition, 2022)
Herein, we developed a dual fluorescent aptasensor based on mesoporous silica to simultaneously detect sulfadimethoxine (SDM) and oxytetracycline (OTC) in animal-derived foods. We immobilized two types of aptamers modified with FAM and CY5 on the silica surface by base complementary pairing reaction with the cDNA modified with a carboxyl group and finally formed the aptasensor detection platform. Under optimal conditions, the detection range of the aptasensor for SDM and OTC was 3-150 ng/mL (R2 = 0.9831) and 5-220 ng/mL (R2 = 0.9884), respectively. The limits of detection for SDM and OTC were 2.2 and 1.23 ng/mL, respectively. The limits of quantification for SDM and OTC were 7.3 ng/mL and 4.1 ng/mL, respectively. Additionally, the aptasensor was used to analyze spiked samples. The average recovery rates ranged from 91.75 to 114.65% for SDM and 89.66 to 108.94% for OTC, and all coefficients of variation were below 15%. Finally, the performance and practicability of our aptasensor were confirmed by HPLC, demonstrating good consistency. In summary, this study was the first to use the mesoporous silica-mediated fluorescence aptasensor for simultaneous detection of SDM and OTC, offering a new possibility to analyze other antibiotics, biotoxins, and biomolecules.